Strangers, aliens, foreigners : the politics of othering from migrants to corporations - Sonnis-Bell, Marissa; Bell, David Elijah; Ryan, Michelle K. (At the interface/probing the boundaries, 2019)
In our everyday lives we contend with others simultaneously and as a result of contending with ourselves. Strangers, Aliens, Foreigners examines the other from interactions and representations of migrants and refugees to terrorist labels to constructions of the local. We find that inclusive and exclusive identities are often arbitrarily defined along ambiguous lines of class, religion, race, ethnicity, nationality, social status, and geography. However, while arbitrarily defined, there are very tangible consequences for the emotional, physical, and psychological well-being of those constructed as the other, as well as legal or governance implications involving human rights and wider socio-political interactions. This collection examines the political-philosophical understandings of what it means to be, or to construct, the stranger, alien or foreigner. 0Contributors are Marissa Sonnis-Bell, David Elijah Bell, Adina Camenisch, Hanna Jagtenberg, Seraina Muller, Lana Pavic, Michelle Ryan and Tomasso Trillo.